2017
DOI: 10.1038/pr.2017.141
|View full text |Cite
|
Sign up to set email alerts
|

Time to lung aeration during a sustained inflation at birth is influenced by gestation in lambs

Abstract: BackgroundCurrent sustained lung inflation (SI) approaches use uniform pressures and durations. We hypothesized that gestational-age-related mechanical and developmental differences would affect the time required to achieve optimal lung aeration, and resultant lung volumes, during SI delivery at birth in lambs.Methods49 lambs, in five cohorts between 118 and 139 days of gestation (term 142 d), received a standardized 40 cmHO SI, which was delivered until 10 s after lung volume stability (optimal aeration) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(87 citation statements)
references
References 41 publications
2
85
0
Order By: Relevance
“…Although their baseline characteristics did not differ from the 2016 population, they were excluded from the final analysis. For the remaining infants, the not significant but expected increased median maximal SI duration and PEEP level in the lower GA-based subgroup [17], confirms the understanding by the medical team of the individualized stepwise LR maneuvers. In a hindsight, to improve the adherence, more than 6 months should have been probably dedicated to educate the medical team and/or a video recording and reviewing program implemented.…”
Section: Discussionsupporting
confidence: 67%
“…Although their baseline characteristics did not differ from the 2016 population, they were excluded from the final analysis. For the remaining infants, the not significant but expected increased median maximal SI duration and PEEP level in the lower GA-based subgroup [17], confirms the understanding by the medical team of the individualized stepwise LR maneuvers. In a hindsight, to improve the adherence, more than 6 months should have been probably dedicated to educate the medical team and/or a video recording and reviewing program implemented.…”
Section: Discussionsupporting
confidence: 67%
“…We studied surfactant-deficient 124–127 days’ preterm lambs (term ~145 days) born via caesarean section under general anaesthesia to ewes that received 11.7 mg of betamethasone 24 and 48 hours prior to delivery 10. Lambs were instrumented before delivery, including applying a custom-built electrical impedance tomography (EIT) belt around the chest as described in detail previously 21 26. At delivery, the lambs were weighed, placed supine and anaesthesia and analgesia maintained with ketamine and midazolam infusions at doses that suppressed spontaneous breathing.…”
Section: Methodsmentioning
confidence: 99%
“…Peripheral oxygen saturation (SpO 2 ), heart rate, arterial blood pressure (HP48S monitor, Hewlett Packard, Andover, MA, USA), airway pressure, gas flow and tidal volume (Vt) at the airway opening (Florian, Acutronic Medical Systems, Hirzel, Switzerland) were measured continuously from birth. Global and regional lung volume changes were acquired by EIT (Pioneer System, Swisstom, Landquart, Switzerland) at 48 scans/s 21 26 27. Arterial blood analysis was performed at 5 min and every 15 min from birth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous trials to evaluate the efficacy and effectiveness of sustained lung inflation on preterm infants that enrolled preterm infants of different gestational age and birth weight have shown the inconsistent result in short‐term outcomes . Animal studies have shown an inverse relationship between gestational age and lung aeration from sustained lung inflation, so the response to sustained inflation may vary with the size and gestational age of an infant. The SAIL trial performed well under CONSORT assessment and concluded that sustained lung inflation should not be used in this patient population.…”
mentioning
confidence: 99%